Effect of knee sleeves on joint angle variability during gait in older adults: a principal component analysis - Tsuchida, Wakako; Inai, Takuma; Kudo, Shoma; Kobayashi, Yoshiyuki; Fujimoto, Masahiro (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAs the global elderly population increases, maintaining walking ability and minimizing fall risk among older adults is crucial for their health and wellbeing. Knee sleeves are commonly utilized in geriatric sports and rehabilitation to stabilize knee joint movement and enhance gait stability. However, their effects on joint kinematics during walking in healthy older adults, particularly on joint angle variability—a factor associated with fall risk—remain inadequately explored. This study aimed to investigate the influence of knee sleeves on joint angle variability during gait in healthy older adults.MethodsPrincipal component analysis was performed on 16 healthy older adults residing in the community, utilizing 3D spatiotemporal data of the participants’ time-normalized lower limb joint angles throughout the complete gait cycle. The analysis involved a 64 × 1818 input matrix, accounting for 16 participants, two conditions (control and knee sleeves), two walking speeds (normal and fast), three angles, three axes, 101 time points, and two parameters (average and variability). Kinematic waveforms were reconstructed based on the statistical findings to identify notable differences in joint angle variabilities between the conditions.Results and discussionThe outcomes revealed reduced variability in knee and ankle joint angles on the sagittal plane when walking with knee sleeves compared to walking without them. Conversely, an increased variability in hip, knee, and ankle joint angles was observed on the sagittal plane when walking at a fast speed compared to a normal speed. These results suggest that knee sleeves may reduce variability in knee and ankle joint angles during walking in older adults, potentially lowering the risk of falls. This effect appears particularly beneficial during fast-paced walking, where joint angle fluctuations are more pronounced than during normal-speed walking. These findings offer quantitative evidence for the effectiveness of knee sleeves in enhancing walking performance in healthy older adults.